The Basis of Civil Liability for Damages Caused by Artificial Intelligence in Light of General Legal Theory: Comparative Study. - Alhiniti, Yasar; Sadrati, Hanae; Almakhzoumi, Omar; Alsarhan, Majed Falah; Aljahdali, Hani (Journal of Human Security (Librello Publishing House), 2025)
The progressive incorporation of artificial intelligence (AI) into information and communication technologies (ICT) has significantly reshaped contemporary social and professional life. In the current digital environment, computers, internet infrastructures, and AI-driven systems are extensively deployed across multiple sectors. However, alongside the accelerated expansion of AI and information technologies, cybercrime has become an increasingly prominent phenomenon, posing serious risks to the privacy and security of individuals, communities, institutions, and states. Despite its substantial advantages, AI has generated considerable legal and regulatory challenges, particularly in relation to cybercrime and civil liability. This study explores the function of AI within ICT and analyses the ways in which technological advancement contributes to cyber-related threats. It further examines the conceptual foundations of civil liability and assesses how responsibility for harm caused by AI systems is addressed within Moroccan, British, and French legal frameworks. Through a comparative approach, the research evaluates traditional, contractual, and objective civil liability models as they apply to AI-induced damage. Particular attention is given to the Moroccan Civil Obligations Code (MOCC), which establishes the basis for liability, and its comparison with corresponding provisions in British and French law, highlighting their principal strengths and legal implications. The findings indicate that existing civil liability regimes remain capable of offering lawful and equitable compensation mechanisms when adapted to the complex characteristics of AI technologies. The study ultimately underscores the pressing need for Morocco to align its legislative framework with international cooperation initiatives and comparative legal models in order to effectively address the emerging challenges associated with artificial intelligence.